A Cross-Sectional Study of Quality of Life among Brazilian Adults with Type 1 Diabetes Treated with Insulin Glargine: Findings and Implications - Almeida, Paulo H.R.F.; Godman, Brian; Nogueira, Vania dos Santos Nunes [UNESP]; de Lemos, Lívia L.P.; de Assis Acúrcio, Francisco; Guerra-Junior, Augusto A.; de Araújo, Vânia E.; Almeida, Alessandra M.; Alvares-Teodoro, Juliana (American Diabetes Association, 2022)
This article describes a cross-sectional study involving 401 adults with type 1 diabetes treated with insulin glargine in Minas Gerais, Brazil. Health-related quality of life was assessed, and worse scores were found to be associated with a low level of education, self-perceived health reported as poor/very poor, being bedridden and not physically exercised, having seen a doctor more than four times in the past year, and having reported comorbidities and episodes of hypoglycemia.